PENGETAHUAN IBU HAMIL PADA PEMILIHAN KB IUD POST PLASENTA DI PUSKESMAS KECAMATAN CIRACAS TAHUN 2018 - Dina Puji (STIKES MITRA RIA HUSADA, 2018)
KB. Based on the results of the author's preliminary study conducted on pregnant women as many as 10 respondents in Ciracas Subdistrict in 2017 found 80% of pregnant women who did not use KB IUD Post Placenta. The purpose of this study was to determine the relationship of age, education, occupation, interests, information sources and economics with the knowledge of mothers in choosing KB IUD Post Placenta in 2018. This study uses a type of quantitative research and the method used is an analytical method through a cross sectional approach that is to see the relationship between independent variables that include age, education, occupation, interest, information and economic sources on the dependent variable, namely the knowledge of pregnant women on the selection of IUD Post KB Placenta in Ciracas Subdistrict in 2018. The number of respondents in this study was 94 pregnant women. Sampling uses accidental sampling. This research was conducted in Ciracas District in 2018. The results showed that there was a relationship between age at p-value 0.32, education at p-value 0.007, interest at p-value 0.016, source of information at p-value 0.032.The conclusion shows that there is a relationship between age, education, interests, and sources of information with the knowledge of pregnant women in the selection of the Post Placenta contrast IUD. It is expected to increase efforts and work together with puskesmas to make promotive efforts so that pregnant women want to install Post I Placenta KB. Key world :IUD KB, Post PlacentaReference :17 ( 2010-2017)